دور التحليل المالي في الحد من المخاطر الائتمانية بالمصارف التجارية الليبية - الفرجاني, إبراهيم مسعود (Scientific Journal of University of Benghazi, 2020)
The purpose of the research is to know the financial analysis role in limitation of credit risks. In order to achieve the research's goal and test its hypotheses, the research depended upon descriptive analytical method. A questioner has been developed specialized for research goal and distributed on simple random sample consist of (62) individuals from credit employees, financial analysis and credit decisions maker in commercial banks in Benghazi city. The data has been processed using statistical program (SPSS). The research achieved some important results: there is a role of financial analysis for limitation of credit risks using cash percentages, activity percentage, debit percentage, profit, cash influx and directional analysis. Whereas, there is not any role of financial analysis using market percentages and prediction forms for financial failure for limitation of credit risks.